Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Retrogressive Thaw Slumps Produce a Changing Disturbance Regime for Arctic Stream Invertebrates - Maria Dolan; Jordan Musetta‐Lambert; Krista S. Chin; Steven V. Kokelj; Suzanne E. Tank; Jennifer Lento; Michael Power; Joseph M. Culp (Global Change Biology, 2026)
For many Arctic rivers and streams, climate‐driven intensification of permafrost thaw slumping is a major source of disturbance to aquatic habitats. Thaw slumps are dynamic landforms that severely increase total suspended solids (TSS) and nutrients in downstream reaches and can persist over decades. Effects may differ in magnitude as slumps cycle through periods of higher and lower activity, with expansion of retrogressive slumps increasing over time. Increases in TSS are known to cause reduced invertebrate abundance and diversity in impacted watersheds; however, it remains unclear if water quality and critical aquatic biodiversity have recovered after prolonged exposure to slumps. Here, we examined decadal‐scale effects of slumps and environmental change on benthic macroinvertebrates (BMI) by comparing environmental and BMI data collected between 2010–2014 and a recent sampling campaign from 2021. High TSS and nutrient concentrations observed during 2010–2014 persisted in slump‐impacted sites in 2021, with no significant change in TSS and total nutrient concentrations after the 10‐year exposure period. TSS continued to act as a nonspecific stressor on BMI, as abundance remained significantly lower in impacted streams compared to reference streams. Although total abundance within reference and impacted sites did not differ significantly between sampling periods, abundance and richness of disturbance tolerant taxa was greater in 2021 as compared to 2010–2014 across all sites, with differences linked to lower precipitation in 2021. These community compositional changes were reflected in increased Shannon‐Weiner diversity between sampling campaigns. Overall, the number of thaw slumps upstream was an important driver of both BMI abundance and diversity across sampling periods and will likely continue to be an important determinant of benthic macroinvertebrate communities as the number and size of thaw slumps continues to increase across the circumpolar Arctic.

Method choice affects estimates of diet and niche breadth for small stream fish - Adam Kuhrt; Jordan Musetta-Lambert; Michael Power; Milla Rautio; Joseph Culp (Hydrobiologia, 2024)

Dominance of net autotrophy in arid landscape low relief polar lakes, Nunavut, Canada - Paola Ayala‐Borda; Matthew J. Bogard; Guillaume Grosbois; Vilmantas Prėskienis; Joseph M. Culp; Michael Power; Milla Rautio (Global Change Biology, 2024)
The Arctic is the fastest warming biome on the planet, and environmental changes are having striking effects on freshwater ecosystems that may impact the regional carbon cycle. The metabolic state of Arctic lakes is often considered net heterotrophic, due to an assumed supply of allochthonous organic matter that supports ecosystem respiration and carbon mineralization in excess of rates of primary production. However, lake metabolic patterns vary according to regional climatic characteristics, hydrological connectivity, organic matter sources and intrinsic lake properties, and the metabolism of most Arctic lakes is unknown. We sampled 35 waterbodies along a connectivity gradient from headwater to downstream lakes, on southern Victoria Island, Nunavut, in an area characterized by low precipitation, organic‐poor soils, and high evaporation rates. We evaluated whether lakes were net autotrophic or heterotrophic during the open water period using an oxygen isotopic mass balance approach. Most of the waterbodies were autotrophic and sites of net organic matter production or close to metabolic equilibrium. Autotrophy was associated with higher benthic primary production, as compared to its pelagic counterpart, due to the high irradiance reaching the bottom and efficient internal carbon and nutrient cycling. Highly connected midstream and downstream lakes showed efficient organic matter cycling, as evidenced by the strong coupling between gross primary production (GPP) and ecosystem respiration, while decoupling was observed in some headwater lakes with significantly higher GPP. The shallow nature of lakes in the flat, arid region of southern Victoria Island supports net autotrophy in most lakes during the open water season. Ongoing climate changes that lengthen the ice‐free irradiance period and increase rates of nutrient evapoconcentration may further promote net autotrophy, with uncertain long‐term effects for lake functioning.

Fatty-acid based assessment of benthic food-web responses to multiple stressors in a large river system - Danny C.P. Lau; Robert B. Brua; Willem Goedkoop; Joseph M. Culp (Environmental Pollution, 2023)

Stream macroinvertebrate community responses to an agricultural gradient alter consumer-driven nutrient dynamics - Heather A. Loomer; Karen A. Kidd; Maitane Erdozain; Glenn A. Benoy; Patricia A. Chambers; Joseph M. Culp (Hydrobiologia, 2023)

Effects of prolonged sedimentation from permafrost degradation on macroinvertebrate drift in Arctic streams - Brianna Levenstein; Jennifer Lento; Joseph Culp (Limnology and Oceanography, 2021)
Retrogressive thaw slumps are areas of unstable degraded permafrost that often drain into nearby watersheds, leading to increased sediment loads and changes in water quality. Thaw slumps are prevalent across the Arctic, including western Canada, Alaska, and Russia, and high‐altitude areas of western China. Over the past several decades, increased temperatures and precipitation in the Arctic have led to increases in the size and frequency of thaw slumps. Our study explored the effects of prolonged sedimentation from thaw slumps in the Peel Plateau, NWT, Canada on benthic macroinvertebrate drift, an important biological function of stream ecosystems. Though sedimentation is known to initiate a catastrophic drift response, studies have generally not considered the drift response to ongoing, long‐term perturbation. Drift densities and sediment loads were measured using drift nets and sediment traps at paired sites upstream and downstream of thaw slumps. We compared drift densities and sediment loads between sites and examined how drift differed over a fine‐sediment gradient. The amount of suspended and settling fine sediments increased significantly at downstream sites. Drift densities decreased at downstream sites; however, when drift was corrected for benthic abundance at each site, there was an increase in proportional drift density associated with increased fine sediments. These results indicate that prolonged impacts from thaw slumps result in lower macroinvertebrate abundance and higher proportional drift relative to undisturbed sites. Ultimately, increased sediment loads from thaw slumps represent a chronic stressor that will continue to prevent recovery of macroinvertebrate communities at impacted sites until these features stabilize.

Developing metabolomics-based bioassessment: crayfish metabolome sensitivity to food and dissolved oxygen stress - Natalie M. Izral; Robert B. Brua; Joseph M. Culp; Adam G. Yates (Environmental Science and Pollution Research, 2018)

Arrowhead (Sagittaria cuneata) as a bioindicator of nitrogen and phosphorus for prairie streams and wetlands - Katherine M. Standen; Patricia A. Chambers; Joseph M. Culp (Wetlands Ecology and Management, 2018)
The emergent aquatic plant, Sagittaria cuneata, is an easily-identified and commonly-found species in the Great Plains region of North America and has the potential to be a bioindicator of nitrogen (N) and phosphorus (P) because of its previously-identified leaf plasticity in response to nutrient conditions. To identify associations between leaf morphology and soil and water nutrients, we conducted: (1) a 10-week controlled experiment in which plants were grown in nutrient-enriched sediment, nutrient-enriched water, or unamended control trials, and (2) a field study where emergent leaves were collected from 15 streams of varying nutrient concentrations. Plants grown in experimentally enriched sediment were more productive than those grown in enriched water or control conditions: they produced more emergent leaves and tubers, had a larger final biomass and height, and developed emergent leaves that showed a consistent increase in size and unique change in shape over time. Emergent leaves collected from field plants also showed significant variability of leaf traits; however, this variability occurred at all scales of replication (leaf, plant, quadrat, and site), with linear mixed effects modelling indicating that random chance was likely driving this variability. Although sediment nutrients were crucial to successful growth of S. cuneata under controlled conditions, the high variability in leaf morphology under field conditions (likely due to large natural variability at the species, population, and individual scale) make leaf plasticity of S. cuneata unsuitable as a bioindicator. Our results emphasize the need to quantify within and among plant variation in leaf morphology (and to clarify sampling methods) for the many taxa of aquatic macrophytes that are phenotypically plastic and notoriously difficult to classify.

Permafrost thaw and intense thermokarst activity decreases abundance of stream benthic macroinvertebrates - Krista S. Chin; Jennifer Lento; Joseph M. Culp; Denis Lacelle; Steven V. Kokelj (Global Change Biology, 2016)
Intensification of permafrost thaw has increased the frequency and magnitude of large permafrost slope disturbances (mega slumps) in glaciated terrain of northwestern Canada. Individual thermokarst disturbances up to 40 ha in area have made large volumes of previously frozen sediments available for leaching and transport to adjacent streams, significantly increasing sediment and solute loads in these systems. To test the effects of this climate‐sensitive disturbance regime on the ecology of Arctic streams, we explored the relationship between physical and chemical variables and benthic macroinvertebrate communities in disturbed and undisturbed stream reaches in the Peel Plateau, Northwest Territories, Canada. Highly disturbed and undisturbed stream reaches differed with respect to taxonomic composition and invertebrate abundance. Minimally disturbed reaches were not differentiated by these variables but rather were distributed along a disturbance gradient between highly disturbed and undisturbed sites. In particular, there was evidence of a strong negative relationship between macroinvertebrate abundance and total suspended solids, and a positive relationship between abundance and the distance from the disturbance. Increases in both sediments and nutrients appear to be the proximate cause of community differences in highly disturbed streams. Declines in macroinvertebrate abundance in response to slump activity have implications for the food webs of these systems, potentially leading to negative impacts on higher trophic levels, such as fish. Furthermore, the disturbance impacts on stream health can be expected to intensify as climate change increases the frequency and magnitude of thermokarst.

A method to regenerate the damaged Chironomidae slides in entellan mounting solution - Armin Namayandeh; Joseph Culp (Journal of Paleolimnology, 2015)

Stream biomonitoring using macroinvertebrates around the globe: a comparison of large-scale programs - Daniel F. Buss; Daren M. Carlisle; Tae-Soo Chon; Joseph Culp; Jon S. Harding; Hanneke E. Keizer-Vlek; Wayne A. Robinson; Stephanie Strachan; Christa Thirion; Robert M. Hughes (Environmental Monitoring and Assessment, 2015)

Fin tissues as surrogates of white muscle when assessing carbon and nitrogen stable isotope levels for Arctic and brook char - R. Allen Curry; Mark D. Gautreau; Joseph M. Culp (Environmental Biology of Fishes, 2014)

Can nutrients mask community responses to insecticide mixtures? - Alexa C. Alexander; Ana T. Luis; Joseph M. Culp; Donald J. Baird; Allan J. Cessna (Ecotoxicology, 2013)

Seasonal Variation in Nutrient Export Along Streams in the Northern Great Plains - Julie Corriveau; Patricia A. Chambers; Joseph M. Culp (Water, Air, & Soil Pollution, 2013)

Single Versus Combined Lethal Effects of Three Agricultural Insecticides on Larvae of the Freshwater Insect Chironomus dilutus - Heidi M. K. LeBlanc; Joseph M. Culp; Donald J. Baird; Alexa C. Alexander; Allan J. Cessna (Archives of Environmental Contamination and Toxicology, 2012)

Evaluation of Deposited Sediment and Macroinvertebrate Metrics Used to Quantify Biological Response to Excessive Sedimentation in Agricultural Streams - Andrew B. Sutherland; Joseph M. Culp; Glenn A. Benoy (Environmental Management, 2012)

Comparison of benthic macroinvertebrate communities by two methods: Kick- and U-net sampling - Robert B. Brua; Joseph M. Culp; Glenn A. Benoy (Hydrobiologia, 2011)

Cadmium Toxicity and Uptake by Mats of the Freshwater Diatom: Navicula pelliculosa (Bréb) Hilse - Elaine C. Irving; Donald J. Baird; Joseph M. Culp (Archives of Environmental Contamination and Toxicology, 2009)

Acute and Chronic Toxicity of Imidacloprid to the Aquatic Invertebrates Chironomus tentans and Hyalella azteca under Constant- and Pulse-Exposure Conditions - Sarah J. Stoughton; Karsten Liber; Joseph Culp; Allan Cessna (Archives of Environmental Contamination and Toxicology, 2008)

Development of a New Approach to Cumulative Effects Assessment: A Northern River Ecosystem Example - Monique Dubé; Brian Johnson; Gary Dunn; Joseph Culp; Kevin Cash; Kelly Munkittrick; Isaac Wong; Kathlene Hedley; William Booty; David Lam; Oskar Resler; Alex Storey (Environmental Monitoring and Assessment, 2006)

Northern Rivers Ecosystem Initiative: Nutrients and Dissolved Oxygen – Issues and Impacts - Patricia A. Chambers; Joseph M. Culp; Nancy E. Glozier; Kevin J. Cash; Fred J. Wrona; Leigh Noton (Environmental Monitoring and Assessment, 2006)